Aquatic life support course manual. 1st ed. - Abdull Wahab, Shaik Farid; Lim, Khai Yen; Abdul Khalil, Amira Farhana; Mohd Mustamam, Adila Hana; Mohamed, Ahmad Suhailan; Sjamun Sjahid, Afifah; Cheah, Kim Siong; IsmailI, Ahmad Khaldun; Kanesan, Kogulan; Rusli, Alif Awatif; Abd. Wahab, Mahathar; Jamal, Ahmad Amirin; et al. (Aquatic Life Support Society, 2022)
Aquatic life support course manual (First edition) is the course manual created to provide aquatic rescue skills and knowledge for the medical personnel. The learning materials regarding aquatic rescue skills and the management of water related incidents were taken from various sources. It also gathers input from various agencies in Malaysia that involved in water safety and rescue. From all the information gathered a syllabus that suits the settings for Malaysian waters is created.